Osteoclasts protect bone blood vessels against senescence through the angiogenin/plexin-B2 axis - Xiaonan Liu (Nature Portfolio, 2021)
Glucocorticoids (GCs) inhibit bone angiogenesis and affect bone development, but the underlying mechanisms remain unclear. Here, the authors show that GCs induce vascular cell senescence during bone development by inhibiting angiogenin secretion from osteoclasts, impairing angiogenesis via endothelial Plexin B2, resulting in unpaired bone growth.